Design and development of software for optimal material cost estimating on aluminum works - Zaragoza Grife, Jesus Nicolas; Solis Carcaño, Romel Gilberto; Gonzalez Fajardo, Jose Antonio (Revista de la Construcción. Journal of Construction, 2014)
One of the main subsystems of any building is the one that generates surroundings, divisions and communication forms between spaces. In many kinds of buildings this is achieved with constructive elements made of aluminum, crystal sheets and other materials. For cost estimating purposes on these elements, waste factors which could vary between different construction sites are carried out for each material involved. This generates a high uncertainty in the cost and the profit as well. The main objective for this research was to develop an extension on a preexistent cost estimating software (SincoWfi) for budget optimization on aluminum works. Functions and the uCalc GNCutter32x components for modeling and optimization solution parameterized cut materials were used. The recommendations of the ICONIX methodology were followed in this development. It was concluded that combining different disciplines and areas of knowledge was possible to obtain an integrated cost estimate and optimize use of materials focused on developing constructive elements whose dimensions can be parameterized in 1D and 2D.